2021
DOI: 10.1016/j.ijid.2020.10.046
|View full text |Cite
|
Sign up to set email alerts
|

The role of case importation in explaining differences in early SARS-CoV-2 transmission dynamics in Canada—A mathematical modeling study of surveillance data

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Québec is unique among Canadian provinces for its early spring break, which resulted in many returning travelers before border closures and quarantine measures were enacted. Our results are consistent with mathematical modelling results (Godin et al 2021) suggesting that Québec’s large and severe SARS-CoV-2 epidemic was driven by this early spring break. Even if most introduction events likely occurred well after spring break, those that arrived during or just after spring break generated the largest transmission lineages.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Québec is unique among Canadian provinces for its early spring break, which resulted in many returning travelers before border closures and quarantine measures were enacted. Our results are consistent with mathematical modelling results (Godin et al 2021) suggesting that Québec’s large and severe SARS-CoV-2 epidemic was driven by this early spring break. Even if most introduction events likely occurred well after spring break, those that arrived during or just after spring break generated the largest transmission lineages.…”
Section: Discussionsupporting
confidence: 92%
“…Before federally mandated quarantine orders for returning travelers were put in place on March 25 th , 1,544 travelers who entered Québec had tested positive with COVID-19 (Godin et al 2021). However, not all these cases were necessarily independent introduction events, nor would they all give rise to successful onward transmission of SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of our study include our use of observed cases, and thus we may underestimate the co-Gini if testing rates were lower among marginalized communities in particular, especially due to testing capacity constraints that were especially salient in the first wave (48-50). Second, although we excluded residents of long-term care homes, our definition of community-wide cases could still include other congregate-level settings such as shelters and group homes reflecting other ‘unmeasured’ determinants that could lead to geographical concentration within cities.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of these triggers is important for slowing down the spread of a pathogen and is, thus, a strategy for public health security. Although imported cases are easier to manage, community transmissions are hard to trace, can grow quickly, and easily threaten local public health systems [16].…”
Section: Principal Findingsmentioning
confidence: 99%